1992
DOI: 10.1007/bf00994613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kairomones from egg and female adult stages ofOstrinia nubilalis (H�bner) (Lepidoptera, Pyralidae) onTrichogramma brassicae Bezdenko (Hymenoptera, Trichogrammatidae) female kinesis

Abstract: Volatile chemicals emanating from the different developmental stages ofOstrinia nubilalis Hübner (Lepidoptera, Pyralidae) increase the mobility ofTrichogramma brassicae Bezdenko (Hymenoptera, Trichogrammatidae) in a linear airflow olfactometer. In this paper, we have demonstrated that airborne chemicals from egg masses and virgin females during calling activity stimulate an intensive search behavior byTrichogramma females. On the other hand, emanations from mated females with extruded abdominal tips do not inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Among the Trichogrammatidae, T. brassicae (Renou et al 1989, 1992, Frenoy et al 1992 and T. ostriniae Pang and Chen (Bai et al 2004, Yong et al 2007 were the most investigated. Females of T. brassicae responded in a linear olfactometer to Ostrinia nubilalis Hübner eggs, and to chemical extracts from eggs of O. nubilalis and M. brassicae.…”
Section: Volatile Kairomones From Host Eggsmentioning
confidence: 99%
“…Among the Trichogrammatidae, T. brassicae (Renou et al 1989, 1992, Frenoy et al 1992 and T. ostriniae Pang and Chen (Bai et al 2004, Yong et al 2007 were the most investigated. Females of T. brassicae responded in a linear olfactometer to Ostrinia nubilalis Hübner eggs, and to chemical extracts from eggs of O. nubilalis and M. brassicae.…”
Section: Volatile Kairomones From Host Eggsmentioning
confidence: 99%
“…Trichogramma parasitoids utilise sex pheromones from calling moths to locate their host (Noldus et al, 1985;Noldus, 1988;Frenoy et al, 1992;Colazza et al, 1997;Fiaboe et al, 2003). In addition, the egg itself can be a direct source of kairomones (Frenoy et al, 1992;Boo & Yang, 2000) and recently oviposition-inducing plant cues have been reported to arrest Trichogramma parasitoids (Fatouros et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the egg itself can be a direct source of kairomones (Frenoy et al, 1992;Boo & Yang, 2000) and recently oviposition-inducing plant cues have been reported to arrest Trichogramma parasitoids (Fatouros et al, 2005). In a field experiment, Lewis et al (1982) reported an increase of parasitism rate on Heliothis zea eggs by Trichogramma spp., on cotton plots treated with a synthetic pheromone blend of H. zea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations